2010
DOI: 10.1136/gut.2010.216135
|View full text |Cite
|
Sign up to set email alerts
|

Combination 5-fluorouracil, folinic acid and cisplatin (LV5FU2-CDDP) followed by gemcitabine or the reverse sequence in metastatic pancreatic cancer: final results of a randomised strategic phase III trial (FFCD 0301)

Abstract: PurposeGemcitabine is the standard chemotherapy for patients with metastatic pancreatic adenocarcinoma. Although the 5-fluorouracil (5FU), folinic acid and cisplatin combination (LV5FU2-CDDP) is an option, the optimal order of the regimens must be determined. The first strategic phase III trial comparing LV5FU2-CDDP followed by gemcitabine versus gemcitabine followed by LV5FU2-CDDP was conducted.MethodsPatients with metastatic pancreatic adenocarcinoma, performance status (PS) 0–2, without prior chemotherapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 32 publications
(14 reference statements)
1
25
0
2
Order By: Relevance
“…It is difficult to conduct a clinical trial for second-line chemotherapy in advanced pancreatic cancer due to the rapidly progressive nature of the general condition and the lack of agents active in pancreatic cancer. However, it has been reported that 55-60% of patients had a relatively good PS following the failure of first-line therapy; thus, physicians should consider second-line therapy in such patients (14).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to conduct a clinical trial for second-line chemotherapy in advanced pancreatic cancer due to the rapidly progressive nature of the general condition and the lack of agents active in pancreatic cancer. However, it has been reported that 55-60% of patients had a relatively good PS following the failure of first-line therapy; thus, physicians should consider second-line therapy in such patients (14).…”
Section: Discussionmentioning
confidence: 99%
“…A significant percentage of MPA patients (about 60%) progressing after gemcitabine-based chemotherapy are still in relatively good clinical condition and may require a second and even a third line of therapy [18]. However, a standard treatment for patients resistant to gemcitabine has not been established to date.…”
Section: Introductionmentioning
confidence: 99%
“…According to the NCCN Clinical Practice Guidelines in Oncology (version 2.2012) [13], the regimen includes capecitabine, 5-fluorouracil (5-FU)/leucovorin/oxaliplatin [9] and capecitabine/oxaliplatin [10] as options. However, after the failure of a gemcitabine-based first-line chemotherapy, there is no accepted active standard second-line treatment of benefit, even if a considerable percentage of patients display good functional condition and a relatively low tumor burden [14,15]. …”
Section: Introductionmentioning
confidence: 99%